Oestrus ovis ophthalmomyiasis acquired in the UK: case report and scanning electron microscopic study. Issue 11 (November 1991) - Stevens, J. D.; McCartney, A. C.; Howes, R.
Abstract : A case of external ophthalmomyiasis acquired in the UK is reported. Oestrus ovis infestation of the external conjunctiva is described and a scanning electron microscopic study made of the first stage larvae. To our knowledge this represents only the third case reported of UK acquisition of ophthalmomyiasis.